2017
DOI: 10.18632/oncotarget.17702
|View full text |Cite
|
Sign up to set email alerts
|

A novel immunotherapy targeting MMP-14 limits hypoxia, immune suppression and metastasis in triple-negative breast cancer models

Abstract: Matrix metalloproteinase-14 (MMP-14) is a clinically relevant target in metastatic cancers due to its role in tumor progression and metastasis. Since active MMP-14 is localized on the cell surface, it is amenable to antibody-mediated blockade in cancer, and here we describe our efforts to develop novel inhibitory anti-MMP-14 antibodies. A phage-displayed synthetic humanized Fab library was screened against the extracellular domain of MMP-14 and a panel of MMP14-specific Fabs were identified. A lead antibody th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…However, the high similarity of protein folding and catalytic chemistry among MMP family members presents a daunting challenge for the generation of highly selective compound inhibitors (Turk, ). Our studies (Lopez, Nam, Kaihara, Mustafa & Ge, ; Nam, Fang, Rodriguez, Lopez, & Ge, ; Nam, Rodriguez, Remacle, Strongin, & Ge, ), among others (Appleby et al, ; Devy et al, ; Ling et al, ; Udi et al, ), demonstrated the feasibility that antibody‐based inhibitors could exhibit the desired high selectivity. Particularly, Fab3A2 with 4.8 nM affinity, 9.7 nM potency, and high selectivity toward MMP‐14 was isolated from a library containing ultralong CDR H3s (Nam et al, ).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, the high similarity of protein folding and catalytic chemistry among MMP family members presents a daunting challenge for the generation of highly selective compound inhibitors (Turk, ). Our studies (Lopez, Nam, Kaihara, Mustafa & Ge, ; Nam, Fang, Rodriguez, Lopez, & Ge, ; Nam, Rodriguez, Remacle, Strongin, & Ge, ), among others (Appleby et al, ; Devy et al, ; Ling et al, ; Udi et al, ), demonstrated the feasibility that antibody‐based inhibitors could exhibit the desired high selectivity. Particularly, Fab3A2 with 4.8 nM affinity, 9.7 nM potency, and high selectivity toward MMP‐14 was isolated from a library containing ultralong CDR H3s (Nam et al, ).…”
Section: Introductionmentioning
confidence: 61%
“…Our studies (Lopez, Nam, Kaihara, Mustafa & Ge, 2017;Nam, Fang, Rodriguez, Lopez, & Ge, 2017;Nam, Rodriguez, Remacle, Strongin, & Ge, 2016), among others (Appleby et al, 2017;Devy et al, 2009;Ling et al, 2017;Udi et al, 2015), demonstrated the feasibility that antibody-based inhibitors could exhibit the desired high selectivity.…”
mentioning
confidence: 65%
“…However, gelatin is a substrate for multiple proteases, and MMPs were expressed on the surface of yeast cells (Diehl et al, 2011), which are quite different from mammalian cell surfaces. As several selective and/or secondary binding site (exosite) MT1-MMP inhibitors have been described (Levin, Udi, Solomonov, & Sagi, 2017;Ling et al, 2017;Pahwa et al, 2014;Santamaria & de Groot, 2018), the evaluation of activity at the cell surface will allow for examination of such inhibitors in a more native-like environment. This will also facilitate the development of inhibitors that may act indirectly on MT1-MMP activity.…”
Section: Discussionmentioning
confidence: 99%
“…Other inhibitory molecules include Fab R2C7 which is highly selective for MMP‐14 (Lopez, Nam, Kaihara, Mustafa, & Ge, ). Another MMP‐14 inhibitor that inhibits the catalytic domain of MMP‐14, Fab 3369, prevents the ECM degradation by MMP‐14 invasion of MDA‐MB‐231 cells (Ling et al, ). The blockade of MMP‐14 has been shown to overcome the immunosuppressive TME in metastatic cases BC (Li et al, ).…”
Section: Immune Checkpoint Inhibitors (Icis)mentioning
confidence: 99%
“…One of the MMP family members, MMP-14 can degrade collagen, which is required for invadopodia formation (Leong et al, 2014). Targeting the metastasis early events for example the degradation step of ECM and the cancer cells invasion, may proved beneficial effects in TNBC (Ling et al, 2017).…”
Section: Icis Combined With Anti-mmp-14mentioning
confidence: 99%